A novel strategy of transition-metal doping to engineer absorption of carbon dots for near-infrared photothermal/photodynamic therapies. (August 2018) - Guo, Xiao-Lu; Ding, Zhao-Yang; Deng, Si-Min; Wen, Chang-Chun; Shen, Xing-Can; Jiang, Bang-Ping; Liang, Hong
Abstract: It is of extreme importance to engineer the structural characteristics of carbon dots (CDs) to satisfy their practical applications in imaging and medical treatments. Here, Cu, N-doped CDs ( Cu, N -CDs) are a new class of near-infrared-(NIR) light-induced therapeutic agents that were prepared by a one-step hydrothermal method using EDTA·2Na and CuCl2 . Specifically, Cu ΙΙ was located in the inner of Cu, N -CDs via N-Cu-N complexation, endowing NIR absorption for the production of heat and reactive oxygen species. The relationships between the hydrothermal temperature, NIR absorption, and intrinsic biological activity of the Cu, N -CDs were examined. The hydrothermal temperature significantly affected the latter two when the Cu content in the Cu, N -CDs was changed. The Cu, N -CDs at 180 °C were examined for cancer phototherapeutics in vitro and in vivo . The Cu, N -CDs markedly inhibited cancer via synergistic photothermal/photodynamic therapies. In addition, the Cu, N -CDs could also act as one kind of fluorescence cell-imaging agent and IR thermal imaging agent to visualize the in vitro and in vivo treatment process, respectively. Thus, the present study provides a promising new method to prepare CDs with NIR absorption feature for multifunctional cancer theranostic applications. Graphical abstract: Image 1